Hadrian and the Christians - Rizzi, Marco (Millennium-Studien / Millennium Studies, 2010)
The book sheds new light on a much debated issue in the field of ancient history: the spread of Christianity in the Roman Empire and its relationship with Judaism in the 2nd century. The contributions collected in this volume illustrate from a multidisciplinary perspective (including archaeology, cultural, religious, and political history) how Christianity found a peculiar way of integrating into the transforming empire under Emperor Hadrian. In this way, Christianity gained an increasing place within Roman society, which ultimately opened the door to its affirmation in subsequent centuries.